Raf-1 N-terminal sequences necessary for Ras-Raf interaction and signal transduction. - Pumiglia, K (1995)
Raf-1 is a serine/threonine protein kinase that transduces signals from cell surface receptors to the nucleus. Interaction of Ras with a regulatory domain in the N-terminal half of Raf-1 is postulated to regulate Raf-1 protein kinase and signaling activities. To better understand molecular interactions of Ras with Raf-1 and regulation of the Raf-1 kinase, a panel of Raf-1 N-terminal mutants expressed in the baculovirus-insect cell system was used for mapping the precise region necessary for Ras interaction in the context of full-length, functional Raf-1 kinase. An 80-amino-acid sequence in Raf-1 between positions 53 and 132 was found to confer the ability to bind Ras protein in vitro and in infected insect cells. Deletion of residues 53 to 132 abolished Raf-1 kinase activation by Ras in insect cells, indicating that activation of the Raf-1 kinase by Ras requires the capacity to physically interact with Ras. By contrast, deletion of this Ras-binding site did not diminish activation of Raf-1 kinase by Src, implying that Src and Ras can activate Raf-1 through independent mechanisms. Significantly, Raf-1 mutants lacking the entire zinc finger motif or containing substitutions of two critical cysteine residues in the zinc finger retained the ability to bind Ras and to be activated by this interaction. Consistent with results obtained in the baculovirus-insect cell system, deletion of residues 53 to 132 but not mutations in the zinc finger motif abrogated the ability of kinase-inactive, dominant negative Raf-1 to block Ras-mediated signaling in Xenopus oocytes. Together, these results provide evidence that the direct physical interaction of Ras with Raf-1 amino acids 53 to 132 is required for activation of the Raf-1 kinase and signaling activities by Ras but not by Src. Furthermore, the adjacent zinc finger motif in Raf-1 is not essential either for interaction with Ras or for activation of the Raf-1 kinase.